Factors influencing employee readiness for organizational change in Malakoff Corporation Berhad, Kuala Lumpur / Asma Wahidah Abd Aziz - Abd Aziz, Asma Wahidah (Faculty of Business and Management, 2018)
The purpose of this study was to determine factors that influenced employee readiness to organizational change in Malakoff Corporation Berhad, Kuala Lumpur. Individual levels of readiness towards change were assessed to determine if there were differences in levels of readiness and relationship with peer-supervisor, perceived organizational justice and communication overload. Demographic variables were also assessed to determine whether a relationship existed with change readiness. This research is quantitative research which used the self-administered questionnaires as instruments to collect data. The data had been collected from 103 of 140 respondents which withdrawn from the total 220 element of population by using simple random sampling method. The data collected is then evaluated by using Statistical Package for the Social Science (SPSS) Version 23.0. Thus, Multiple Regression analysis indicates that there are significant relationship between organizational justice and communication overload with employee readiness for change. However, no significant relationship between workplace relations and employee readiness. Regression analysis also reveals that organizational justice is the most influential factors towards employee readiness for organizational change in Malakoff Corporation Berhad, Kuala Lumpur.